2003
DOI: 10.1034/j.1600-0897.2003.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase Activity and Pregnancy‐Associated Differences in Immunologically Relevant Peripheral Blood Leukocyte Populations

Abstract: Elevated BuChE activity in normal pregnancy may correlate with better ability to clear pregnancy-threatening toxins, while lesser ability to do this in PIH women may be a contributor to disease. The fact that PIH subjects with large subpopulations of activated T cells also exhibited low BuChE activity further suggests a correlation between susceptibility to pregnancy loss and decreased activity of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Association of the K variant (1615nt: GCA→ACA; Ala539Thr) of this gene with type 2 diabetes mellitus was reported in one study [1] and not confirmed by another [2]. Considering that the K variant is associated with 30% reduction in BChE activity [3] and that low BChE activity was related to immune dysfunction [4], the hypothesis that this variant may be positively associated with type 1 diabetes mellitus (DM1) was tested.…”
Section: (I) Results From Variance Analysis (Anova*) With Type 1 Diabmentioning
confidence: 99%
See 1 more Smart Citation
“…Association of the K variant (1615nt: GCA→ACA; Ala539Thr) of this gene with type 2 diabetes mellitus was reported in one study [1] and not confirmed by another [2]. Considering that the K variant is associated with 30% reduction in BChE activity [3] and that low BChE activity was related to immune dysfunction [4], the hypothesis that this variant may be positively associated with type 1 diabetes mellitus (DM1) was tested.…”
Section: (I) Results From Variance Analysis (Anova*) With Type 1 Diabmentioning
confidence: 99%
“…The present data suggest that the K variant or another variant in linkage disequilibrium with it may predispose to DM1 of earlier onset. The facts that BChE is a biological scavenger for organophosphorus compounds [7] that may provoke immune dysfunction [8] and that low BChE activity may be related to immune dysfunction [4] may be the rationale for the association found between the K variant and DM1 of relatively earlier onset.…”
Section: (I) Results From Variance Analysis (Anova*) With Type 1 Diabmentioning
confidence: 99%
“…Furthermore, as all patients had normal liver and renal functions, this could explain the normal enzyme levels and BMI. Mahmoud et al [10,11] reported that there was evidence that Kuwaiti women experiencing pregnancy disorders, such as pre-eclampsia and diabetes during their pregnancies had lower serum activity of BChE; however, the mechanisms involved in GD have not been fully investigated. Whiteman et al [12] reported that interpregnancy weight gain is associated with a doseresponse increase in the risk of diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the magnitude of the reduction of AChE expression is proportionally related to PE severity [33]. Alternatively, levels and activity of BChE in maternal circulation as well as in fetal umbilical cord blood have been repeatedly shown to be diminished in PE compared with healthy pregnancy [112][113][114][115][116]. Similar decreases in cholinesterase activity have been documented in severe trauma and sepsis [117,118].…”
Section: Pe Modulation Of Acetylcholinesterasesmentioning
confidence: 95%